EDITORIAL - Jaguaribe, Beatriz; Sovik, Liv; Murari, Lucas (Revista Eco-Pós, 2019)
Nota editorial do Dossiê "Novas Faces do Poder: líderes, política, estética, mídia". Revista ECO-Pós v. 22, n. 2, 2019